Psychological resilience and coping strategies with anxiety among Malaysian medical students during the COVID-19 pandemic - Bentham Liang, Sen Teh; Jin, Kiat Ang; Eugene Boon, Yau Koh; Nicholas Tze, Ping Pang (Multidisciplinary Digital Publishing Institute, 2023)
Coronavirus Disease 2019 (COVID-19) swept the world by storm and caused a myriad of devastating consequences, particularly disruptions in medical education. This study aims to examine the association between sociodemographic factors, psychological factors, coping strategies and anxiety among medical students, as well as to identify the predictors of anxiety among them. A cross-sectional study design was used. Self-rated Rosenberg Self-Esteem Scale (RSES), General Self-Efficacy Scale (GSES), Brief Coping Orientation to Problems Experienced Scale (Brief COPE), and General Anxiety Disorder-7 Scale (GAD-7) were used. A total of 371 respondents from a tertiary education center were recruited. The prevalence of anxiety was 37% which corresponded to 21.6% and 15.4% for moderate and severe anxiety, respectively. Sociodemographic factors such as age group and academic year were significantly associated with anxiety, while those with higher self-esteem (rs = −0.487), self-competence (rs = −0.407), self-liking (rs = −0.499), and self-efficacy (rs = −0.245) had lower anxiety. Inversely, those who adopted emotion-focused (rs = 0.130) and dysfunctional coping styles (rs = 0.559) showed higher anxiety. The main predictors of anxiety were self-liking as a protective factor (aOR = 0.81) and dysfunctional coping as a risk factor (aOR = 1.16). Therefore, resilience building and inculcating positive coping strategies are imperative in equipping our budding healthcare providers to weather through future unforeseeable disasters.